Polyarthritis due to systemic lupus erythematosus in a dog - R.M. Krüger; R.T. França; A.S. Amaral; J.E.W. Schossler (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2013)
A five year old male mongrel dog was presented for medical consultation with a history of arthralgia. Complete blood count revealed linfopenia and neutropenia, antinuclear antibody was positive at 1:1,256, and synovial fluid analysis showed inflammatory arthritis with lupus erythematosus cells. No significant proteinuria was detected on urinalysis, and microalbuminuria measurement was performed to determine glomerulonephritis in early stage. Based on clinical signs, synovial fluid analysis, antinuclear antibody test and complete blood count, the diagnosis was systemic lupus erythematosus. The measurement of microalbuminuria was useful to demonstrate the absence of glomerulonephritis, and the performance of complementary tests proved to be indispensable for diagnosis and prognosis. Glucocorticoid treatment led to complete remission.